The Tijani Tariqa Response to the Covid-19 Pandemic in Indonesia - Cucu Setiawan; Muhtar Solihin; Ayi Rahman; Maulani Maulani (UIN Sunan Gunung Djati, 2022)
This article discusses the response of the Tijani congregation at the Zawiyah Islamic boarding school in Garut to the Covid-19 pandemic situation. This research is field research using qualitative methods. This research was conducted at the Zawiyah Islamic Boarding School in Garut, located on Jln. Samarang KM 10 Kampung Surya Tanjung Anom RT 001 RW 010 Samarang Village, Samarang District, Garut Regency, West Java. The data collection technique was through direct observation and in-depth interview techniques, while the data analysis was carried out in a descriptive-analytical way. Based on the data obtained in the research process, the authors found three practices of the Tijani tarekat: wirid (passage of Koran), customary, wadzifah, and hailallah. The practice of wirid and wadzifah are practiced individually in their respective homes. In contrast, the practice of wirid hailalah is carried out in the congregation in the Zawiyah of the Tijani congregation. However, during the Covid-19 pandemic, Sheikh Ikyan urges wirid hailalah to be implemented individually in their respective homes until the Covid-19 pandemic situation improves. Shaykh Ikyan explained that the appeal was a response and cooperation of the Tijani Islamic Boarding School Zawiyah Garut Islamic Boarding School with the government in tackling the Covid-19 outbreak in Indonesia. In addition, the author also found that the Tijani congregation's response to the Covid-19 pandemic situation was to carry out Sheikh Ahmad Tijani's haul in a hybrid way.